PEMBERDAYAAN MASYARAKAT SEKITAR HUTAN DI DESA SUNGAI ARA KABUPATEN PELALAWAN - herman, herman; Rifaí H, Arief; Gesmi, Irwan (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2022)
Sungai Ara Village is one of the villages in Riau Province, precisely in Pelalawan District, Pelalawan Regency where this village is directly adjacent to industrial plantation forests. Through the regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number P.12/Menlhk-II/2015, industrial plantation forests are obliged to empower the community with a forest area of ​​20% to be managed independently by the community with a partnership pattern. The purpose of this service is to provide knowledge, understanding and information to the community regarding the importance of empowering communities around forests and knowing their rights to living plants in industrial forest plantations in the context of productivity in the community's economy. This service is carried out by providing material to participants, then a question and answer session, and ends with a discussion to find solutions to the problems faced. The service participants were 15 people, with details of 5 Village Apparatus including the Village Head, and 10 people from community elements including millennials. It can be concluded that the implementation of community empowerment services obtained satisfactory results with the benefits of knowledge for the community.